2016
DOI: 10.1038/srep31376
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of 134Cs/137Cs in the environment to identify the reactor units that caused atmospheric releases during the Fukushima Daiichi accident

Abstract: The Fukushima Daiichi nuclear power reactor units that generated large amounts of airborne discharges during the period of March 12–21, 2011 were identified individually by analyzing the combination of measured 134Cs/137Cs depositions on ground surfaces and atmospheric transport and deposition simulations. Because the values of 134Cs/137Cs are different in reactor units owing to fuel burnup differences, the 134Cs/137Cs ratio measured in the environment was used to determine which reactor unit ultimately contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 17 publications
2
54
0
Order By: Relevance
“…Such a contrasting size and form; combined with (i) differing radiocesium ratios ( 134 Cs/ 137 Cs) determined in previous works (Chino et al, 2016), (ii) the location at which the samples were obtained and (iii) reactor core modeling (Nishihara et al, 2012), has led many to speculate that each particulate type represents emission from a specific reactor at the Fukushima site (Shibahara et al, 2014;Zheng et al, 2014;Snow et al, 2016).…”
mentioning
confidence: 99%
“…Such a contrasting size and form; combined with (i) differing radiocesium ratios ( 134 Cs/ 137 Cs) determined in previous works (Chino et al, 2016), (ii) the location at which the samples were obtained and (iii) reactor core modeling (Nishihara et al, 2012), has led many to speculate that each particulate type represents emission from a specific reactor at the Fukushima site (Shibahara et al, 2014;Zheng et al, 2014;Snow et al, 2016).…”
mentioning
confidence: 99%
“…A map of 134 Cs: 137 Cs deposition-density ratios over a wide area in eastern Japan indicated regional variation [23], which was analyzed by atmospheric dispersion simulation and using information from reactor analysis [63]. The regional distribution of deposition density ratio obtained from the model simulation showed general agreement with that observed.…”
Section: Identification Of Origin Of Deposited Radionuclidesmentioning
confidence: 56%
“…In particular, the ratio of 134 Cs to 137 Cs is an effective indicator of origin, because the chemical behavior is considered to be the same between the isotopes and the releasedradionuclide ratio is maintained in the deposition density ratio. Reactor analysis results indicated that the 134 Cs: 137 Cs release ratios were 0.94, 1.08, and 1.05 for reactors 1, 2, and 3, respectively, as of March 15, 2011 [63,64].…”
Section: Identification Of Origin Of Deposited Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation
“…These datasets have many data of radionuclides, however, are not available for the investigation of the hourly atmospheric radionuclides concentrations, and might have missed if the polluted air masses passed without precipitation. Hence, the source term identification of plumes still has a large uncertainty, although many studies have been reported (Chino et al, , 2016Katata et al, 2015).…”
Section: Introductionmentioning
confidence: 99%